Trade facilitation and poverty reduction: China-ASEAN region case study - Laping Wu (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2013)
Trade facilitation has been a key part in the opening up process of China. This paper aims to investigate the linkage between trade facilitation and poverty reduction in China. It discusses the impact of the trade facilitation practises in China and the China-ASEAN cooperation on trade between China and ASEAN countries. A provincial panel data set for China from 2000 to 2008 is employed to quantify the impact of agricultural imports, agricultural exports and trade facilitation on poverty. The results show that a 1 per cent increase in port efficiency results in a 1.051 per cent decrease in the poverty index.
Keywords: F15; I3; O24; 330; Trade Facilitation; China; ASEAN; Poverty